2022
DOI: 10.3390/medicina58101392
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delayed Diagnosis of Acute Cholecystitis among Rural Older Patients: A Retrospective Cohort Study

Abstract: Background and objectives: Acute cholecystitis causes acute abdominal pain and may necessitate emergency surgery or intensive antibiotic therapy and percutaneous drainage, depending on the patient’s condition. The symptoms of acute cholecystitis in older patients may be atypical and difficult to diagnose, causing delayed treatment. Clarifying the risk factors for delayed diagnosis among older patients could lead to early diagnosis and treatment of acute cholecystitis. This study aimed to explore the risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A cohort study [ 16 ] showed that older female patients with poor nutritional conditions, including low serum albumin levels, low BMI, vague symptoms and no abdominal pain might have delayed cholecystitis diagnosis. The death case in this study had low METs and low BMI before fracture, although clinical symptoms included abdominal pain without nausea or vomiting, so that the disease condition is also easily overlooked or delayed.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study [ 16 ] showed that older female patients with poor nutritional conditions, including low serum albumin levels, low BMI, vague symptoms and no abdominal pain might have delayed cholecystitis diagnosis. The death case in this study had low METs and low BMI before fracture, although clinical symptoms included abdominal pain without nausea or vomiting, so that the disease condition is also easily overlooked or delayed.…”
Section: Discussionmentioning
confidence: 99%